Sytuacja prawna ofiary przestępstwa w postępowaniu wykonawczym w perspektywie sprawiedliwości naprawczej - Pasoń, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is devoted to the legal situation of a crime victim in the course of executive penal proceedings. The starting point for the considerations was the statement that Goffman’s concept of total institutions and the resulting negative consequences, such as the effects of deculturation or deprivation affecting inmates, are still valid in relation to Polish penitentiary units. It is considered that restorative justice can be an effective instrument for the transition from a total institution to its negation, that is, a permeable institution, especially insofar as it promotes tools for victim and community activation in criminal proceedings. Therefore, the situation of the victim in the current model of executive proceedings was analyzed from the perspective of the possibility of implementing the idea of restorative justice. The subject matter of the article is not limited only to a synthesis of the victim’s rights under the current Executive Penal Code. The provisions normalizing the rights of the victim were analyzed in the context of the whole Code regulation and with reference to the earlier stages of criminal proceedings. In this way a complete and actual picture of the victim’s situation at this stage of criminal proceedings was presented, which was then compared with the standard of restorative justice. The critical analysis made it possible to identify the shortcomings in the current regulation of the victim’s legal situation and to outline the direction in which the legislator should proceed in order to achieve the standard of restorative justice, which will make it possible to increase the permeability of penitentiary units and thus minimize their total character.
Keywords: instytucje totalne; sprawiedliwość naprawcza; pokrzywdzony; prawo karne; postępowanie wykonawcze